A randomized controlled trial to determine the efficacy of vitex negundo L. as treatment for fever - Conching, Raul Martin A.
Introduction: Herbal medicine use has a common place in practically all forms of societies. Its high acceptability and believed or established efficacy and safety could be its strongest attributes. The Department of Health of the Republic of the Philippines embarked on the program of propagation, preparation and advocacy of several identified Herbal Medicines common in the country. Vitex negundo L. (Lagundi) is one of those which has been promoted for the following indications: cough, asthma, pain and fever. Results of case series studies of Lagundi for fever have been variable. The herb is now marketed in 300 mg tablets form by both the government and private sector on the basis of assumed positive results of clinical trials for cough. This study, therefore, was conducted to answer the question of efficacy of Lagundi for fever.